Calcium and ascorbic acid affect cellular structure and water mobility in apple tissue during osmotic dehydration in sucrose solutions - Mauro, Maria A. [UNESP]; Dellarosa, Nicolò; Tylewicz, Urszula; Tappi, Silvia; Laghi, Luca; Rocculi, Pietro; Rosa, Marco Dalla (Elsevier, 2016)
The effects of the addition of calcium lactate and ascorbic acid to sucrose osmotic solutions on cell viability and microstructure of apple tissue were studied. In addition, water distribution and mobility modification of the different cellular compartments were observed. Fluorescence microscopy, light microscopy and time domain nuclear magnetic resonance (TD-NMR) were respectively used to evaluate cell viability and microstructural changes during osmotic dehydration. Tissues treated in a sucrose-calcium lactate-ascorbic acid solution did not show viability. Calcium lactate had some effects on cell walls and membranes. Sucrose solution visibly preserved the protoplast viability and slightly influenced the water distribution within the apple tissue, as highlighted by TD-NMR, which showed higher proton intensity in the vacuoles and lower intensity in cytoplasm-free spaces compared to other treatments. The presence of ascorbic acid enhanced calcium impregnation, which was associated with permeability changes of the cellular wall and membranes.
Keywords: Cell compartments; Cell viability; Mass transfer; Microscopy; NMR